Design and Implementation of Responsive Digital Signature Pad Using Web Technologies - Dr. G. Sreedhar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper presents the design and implementation of a responsive digital signature pad utilizing HTML5 Canvas and JavaScript. The proposed solution enables users to capture handwritten signatures directly within a web browser, facilitating electronic documentation processes. The system’s architecture, user interface design, and underlying code are discussed, highlighting its applicability in various sectors requiring secure and verifiable electronic signatures.